Hepatic TREM2+ macrophages express matrix metalloproteinases to control fibrotic scar formation. Issue 3 (10th January 2023) - Lee, Kyeong‐Jin; An, Seungchan; Kim, Mi‐Yeon; Kim, Sun Myoung; Jeong, Won‐Il; Ko, Hyun‐Jeong; Yang, Yoon Mee; Noh, Minsoo; Han, Yong‐Hyun
Abstract: Liver cirrhosis is characterized by the extensive deposition of extracellular matrix such as fibril collagen, causing dysfunction and failure of the liver. Hepatic macrophages play pivotal roles in the transition from inflammatory to restorative properties upon hepatic injury. In particular, scar‐associated macrophages (SAMacs) control liver fibrosis with the representative expression of matrix metalloproteinase (MMP). However, the heterogenic SAMac population has not been well characterized yet. This study profiled heterogeneous liver macrophages using public databases of single‐cell transcriptomics and found T‐cell immunoglobulin and mucin containing (TIM)4 − macrophages exhibited elevated expression of MMPs. Scar‐associated triggering receptor expressed on myeloid cells (TREM)2 was positively correlated with MMP expression, suggesting that TREM2 + subsets exert their fibrotic role via MMPs. During the progression of diet‐induced nonalcoholic steatohepatitis and drug‐induced liver cirrhosis, monocyte‐derived TREM2 + macrophages accumulate in the liver with the distinct expression of MMPs. A noticeable expansion of MMP‐ and TREM2‐ double positive macrophages was observed in fibrotic scar regions. Consistently, the analysis of single‐cell transcriptomics for human cirrhotic livers supported the theory that TREM2 + SAMacs are strongly associated with MMPs. The results could expand the understanding of liver fibrosis and SAMac, offering potential therapeutic approaches for liver cirrhosis. Abstract : In this work, we found that TREM2 + macrophages within the TIM4 ‐ macrophage population markedly express matrix metalloproteinase (MMP) 12, 13 and 14 to modulate the progression of hepatic fibrosis. The expression of MMPs and TREM2 are positively correlated in liver macrophages. TREM2 + macrophages closely localize to the fibrotic area and control hepatic scar formation via the production of abundant MMPs.